Apuntes sobre la generación del 50 y Palma - Reyes Tarazona, Roberto (2018)
The Traditions of Ricardo Palma have enjoyed great recognition since its appearance, but also they have been object of criticism and disqualification by some intellectuals and writers as Manuel Gonzales Prada, the indigenists and Sebastian Salazar Bondy. The last one, one of the most distinguished key figures from the Generation of ’50, in Lima the Hideous, accuses the traditionist to be the main myth creator of an idyllic Lima and the “colonial Arcadia”; of an ancient vision that should be dismissed for being retrograde. This position has widespread to the rest members of his generation. This article demonstrates that this generalization is erroneous, since most of the members of this generation consider Palma as a classic and recognize his values as creator and in his role in Peruvian literature formation.